SANKSI PIDANA BAGI PELAKU PEMBIARAN TINDAK PIDANA NARKOTIKA DITINJAU DARI UU NO. 35 TAHUN 2009 TENTANG NARKOTIKA - Karisma Ramadhan, Yunus; Sarna, Kadek (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015)
Criminal sanctions for perpetrators of the omission in narcotics crime from prespective of Law No. 35 of 2009 on Narcotics are things that should be known by the whole of society in relation to the obligation to report the occurrence of a crime and society participation to combat and prevent narcotics crime in their neighborhood. Issues that will be discussed is what is sanction for someone who commiting ommision of narcotic crime. The method used is a normative juridical approach, because there is vagueness norm in article 131 Law No. 35 of 2009 on Narcotics about the condition/category of a person who doing omission in narcotic crime. Analysis using way of interpretation and strengthened by the opinion of legal experts. The conclusion is condition/category person considered doing omission narcotic crime when someone is seen directly the occurrence of crime but did not report it to the law enforcement, can be charged with Article 131 Law No.35 of 2009 on Narcotics.
Keywords: Narcotic Crime, Obligation, Society Participation, Criminal Sanction